Nutritional status and feeding practices in pre-school children aged 1-5 years in rural and urban areas of East Azerbaijan- Iran - Abbasalizad Farhangi, Mahdieh (Progress in Nutrition, 2016)
Backgrounds and Objectives: The current study was aimed to investigate the nutritional status of children under five-year of age and its associated factors in East Azerbaijan-Iran. Methods: Four hundred fifteen preschool children referring to public health centers in eight health centers in urban and rural areas of East Azerbaijan-Iran were selected. Nutritional status including height for age (HAZ), weight for age (WAZ) and weight for height Z-scores (WHZ) were calculated using the Epi-Info 2000 using the Centers for Disease Control and Prevention (CDC) 2000 standards. Results: Totally 17 (5.96%), 20 (7.01%) and 21 (7.36%) children from urban and 8 (6.15%), 11 (8.46%) and 11 (8.46%) children from rural areas were underweight, stunted and wasted respectively. The highest prevalence of underweight and wasting was observed in boys from rural areas (8% and 12% respectively); while the highest prevalence of stunting [6 (10.90%)] was observed in the girls of rural areas. The prevalence of severe wasting, stunting and underweight was 2.89%, 2.40% and 4.33% respectively. Weight for age z-score (WAZ) was non-significantly higher in children with proper complementary feeding practices; while all three indices of nutritional status were significantly higher in formula-fed children compared with exclusively-breast fed children (P < 0.05). Conclusion: In conclusion, the high prevalence of malnutrition among children under five-years of age and their poor feeding practices in the current study emphasizes the need for nutrition education and improving behavioral change practices in mothers as a target population.